PENDIDIKAN ISLAM MENGHADAPI GEJOLAK SAINS DAN TEKNOLOGI - Hajiannor, Hajiannor (Fakultas Tarbiyah IAI Darussalam, 2024)
Science and technology are important instruments for the creation of life's progress towards the awakening of the image of a prosperous, prosperous and prosperous humanity in a sustainable living environment. The building of life described in this article calls for guidance so that its presence does not have a devastating negative impact not only on humans but on the environment as a whole. Knowledge, which in Islam's view is one of the means of getting closer to God, should be the control of human attitudes and behavior that are based on ethics of morality and spirituality so that the various activities of life that he does bring good, salvation and happiness to the present world. Facing the current of Iptek development with all its accesses, both positive and negative, Islamic education presents a building of knowledge based on the values of Akidah. With it the implementation of science contains the order of spirituality that brings peace and well-being to one another and all of his creations according to his duty and role as a caliph fi al-ardl.